Antibacterial Effect of Honey-Derived Exosomes Containing Antimicrobial Peptides Against Oral Streptococci - Leiva-Sabadini C (Dove Medical Press, 2021)
Camila Leiva-Sabadini,1 Simon Alvarez,2 Nelson P Barrera,3 Christina MAP Schuh,2,* Sebastian Aguayo1,4,* 1Dentistry School, Faculty of Medicine, Pontificia Universidad Católica de Chile, Santiago, Chile; 2Centro de Medicina Regenerativa, Facultad de Medicina Clínica Alemana-Universidad del Desarrollo, Santiago, Chile; 3Department of Physiology, Faculty of Biological Sciences, Pontificia Universidad Católica de Chile, Santiago, Chile; 4Institute for Biological and Medical Engineering, Schools of Engineering, Medicine and Biological Sciences, Pontificia Universidad Católica de Chile, Santiago, Chile*These authors contributed equally to this work.Correspondence: Christina MAP SchuhCentro de Medicina Regenerativa, Facultad de Medicina Clínica Alemana-Universidad del Desarrollo, Santiago, ChileEmail cschuh@udd.clSebastian AguayoDentistry School, Faculty of Medicine, Pontificia Universidad Católica de Chile, Santiago, ChileEmail sebastian.aguayo@uc.clPurpose: Recently, our group found exosome-like extracellular vesicles (EVs) in Apis mellifera honey displaying strong antibacterial effects; however, the underlying mechanism is still not understood. Thus, the aim of this investigation was to characterize the molecular and nanomechanical properties of A. mellifera honey-derived EVs in order to elucidate the mechanisms behind their antibacterial effect, as well as to determine differential antibiofilm properties against relevant oral streptococci.Methods: A. mellifera honey-derived EVs (HEc-EVs) isolated via ultracentrifugation were characterized with Western Blot and ELISA to determine the presence of specific exosomal markers and antibacterial cargo, and atomic force microscopy (AFM) was utilized to explore their ultrastructural and nanomechanical properties via non-destructive immobilization onto poly-L-lysine substrates. Furthermore, the effect of HEc-EVs on growth and biofilm inhibition of S. mutans was explored with microplate assays and compared to S. sanguinis. AFM was utilized to describe ultrastructural and nanomechanical alterations such as cell wall elasticity changes following HEc-EV exposure.Results: Molecular characterization of HEc-EVs identified for the first time important conserved exosome markers such as CD63 and syntenin, and the antibacterial molecules MRJP1, defensin-1 and jellein-3 were found as intravesicular cargo. Nanomechanical characterization revealed that honey-derived EVs were mostly < 150nm, with elastic modulus values in the low MPa range, comparable to EVs from other biological sources. Furthermore, incubating oral streptococci with EVs confirmed their antibacterial and antibiofilm capacities, displaying an increased effect on S. mutans compared to S. sanguinis. AFM nanocharacterization showed topographical and nanomechanical alterations consistent with membrane damage on S. mutans.Conclusion: Honey is a promising new source of highly active EVs with exosomal origin, containing a number of antibacterial peptides as cargo molecules. Furthermore, the differential effect of HEC-EVs on S. mutans and S. sanguinis may serve as a novel biofilm-modulating strategy in dental caries.Keywords: atomic force microscopy, honey, biofilms, dental caries